An annotated checklist of higher plants in Ayer Hitam Forest Reserve, Puchong, Selangor - Ibrahim, Faridah Hanum; Ibrahim, A. Zainuddin; Khamis, Shamsul; Saleh, Mohd Nazre; Lepun, Philip (Universiti Putra Malaysia Press, 2001)
Ayer Hitam Forest Reserve is a Kelat-Kedondong subtype of the lowland dipterocarp forest situated in the Klang Valley which is currently undergoing a tremendous pace of socio-economic and physical development. The forest had been logged many times in the last 60 years or so and most vegetation niches are beginning to recover to their climax again. Our expedition, from 2-5 May 2000 involved a few botanists who observed and collected specimens of higher plants. The enumeration provided here is based only on the specimens collected during the expedition, includes 262 species of vascular plants belonging to 142 genera and 56 families: The Myrtaceae, with 22 species is the largest family in the checklist, followed by Euphorbiaceae, Dipterocarpaceae and Annonaceae with 21, 17 and 14 species, respectively. Species-wise the genus Knema, is the largest with 13 species, followed by Memecylon, Syzygium and Diospyros with 9, 7, and 7 species, respectively.